THE ROLE OF THE INTEGRATIVE APPROACH IN TEACHING ALISHER NAVOI CREATIVITY - Burkhanova Madinabonu Sayidkamol kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
the article discusses the role of approaches in the effectiveness of the educational process, its types, the uniqueness and importance of the integrative approach, some of its main ideas, the integrative lesson, the role of the integrative approach in studying the works of Alisher Navoi, in particular, in teaching his wisdom.